The influence of transformational leadership and knowledge management on the performance of Indonesian Chamber of Commerce and Industry (Kadin) members, mediated by organizational culture in East Kalimantan Province - Tania, Dayang Donna Walfiaries; Setyadi, Djoko; Mintarti, Sri; Abidin, Zainal (International Journal of Innovative Research and Scientific Studies, 2025)
The Indonesian Chamber of Commerce and Industry (KADIN) is an independent organization that serves as a forum for Indonesian entrepreneurs in various sectors, including trade, industry, and services. The function and role of KADIN as a forum for entrepreneurs brings together entrepreneurs from small to large scales to encourage collaboration. Then, as a partnership with the government, KADIN plays a role as a strategic partner of the government in formulating economic, trade, and industry policies. As for the development of MSMEs, KADIN plays a role in helping the development of Micro, Small, and Medium Enterprises (MSMEs) through training, funding, and market access. KADIN has national, provincial, and district/city management levels, managed by a Board of Directors consisting of entrepreneurs and professionals in various sectors, with training and workshop programs and activities that provide education to increase the capacity of entrepreneurs. Furthermore, investment promotion activities attract foreign investment to Indonesia and expand business networks to the global market, and business forums hold trade exhibitions, conferences, and business dialogues to bring together business actors. With its vision, KADIN supports inclusive and sustainable Indonesian economic growth, and with KADIN's mission to develop a conducive business ecosystem, increase the competitiveness of the business world, and encourage innovation in the economic sector. KADIN collaborates with international business organizations to expand the market and increase the competitiveness of Indonesian products. This study aims to determine the effect of transformational leadership and knowledge management on the performance of KADIN members in East Kalimantan Province. This study describes the causal relationship between variables, or what is called explanatory research, namely a study to determine and explain the influence between existing variables, and is continued with testing of 7 (seven) hypotheses. In this study, the population was 270 KADIN members in East Kalimantan Province. Using WarpPLS 7.0, the author tested 7 (seven) hypotheses in this study. The results found that all variables of transformational leadership, knowledge management, and organizational culture had a positive and significant influence on performance, and organizational culture could mediate transformational leadership and knowledge management. This means that all variables have an important role in improving the performance of KADIN members in East Kalimantan Province.